Dispersing male Parnassius smintheus butterflies are more strongly affected by forest matrix than are females. (10th May 2018) - Goff, Jennifer; Yerke, Catherine; Keyghobadi, Nusha; Matter, Stephen F.
Abstract: Dispersal is a central aspect of the ecology, evolution, and conservation of species. Predicting how species will respond to changing environmental conditions requires understanding factors that produce variation in dispersal. We explore one source of variation, differences between sexes within a spatial population network. Here, we compare the dispersal patterns of male and female Parnassius smintheus among 18 subpopulations over 8 years using the Virtual Migration Model. Estimated dispersal parameters differed between males and females, particularly with respect to movement through meadow and forest matrix habitat. The estimated dispersal distances of males through forest were much less than for females. Observations of female movement showed that, unlike males, females do not avoid forest nor does forest exert an edge effect. We explored whether further forest encroachment in this system would have different effects for males and females by fitting mean parameter estimates to the landscape configuration seen in 1993 and 2012. Despite differences in their dispersal due presumably to both habitat and physiological differences, males and females are predicted to respond in similar ways to reduced meadow area and increased forest isolation.